Improvement of water splitting activity of silver-excess AgTaO3 photocatalysts via nitric acid washing treatment. Issue 4 (August 2022) - Amano, Fumiaki; Nakayama, Satoshi
Abstract: Silver tantalate (AgTaO3 with a bandgap of 3.4 eV) particles loaded with Rh–Cr oxide cocatalyst are used as photocatalysts for water splitting reactions with a high apparent quantum efficiency (AQE). AgTaO3 prepared via solid-state reaction at high temperatures may possess metallic Ag particles on the surface, resulting in Ag + defects in the bulk of the material. These defects result in low activity owing to the increase in the recombination of photogenerated electrons and holes. Therefore, adding Ag in excess to suppress the formation of Ag + defects would improve the photocatalytic activity of AgTaO3 . In contrast, the excess Ag forms numerous metallic Ag particles on the AgTaO3 surface, which decrease the photocatalytic activity owing to the electron migration to the Ag particles. This study investigated the effectiveness of washing treatments using concentrated HNO3 to remove the metallic Ag particles formed on the Ag-excess AgTaO3 surface. After loading the Rh0.5 CrO x cocatalyst, the water splitting activity of AgTaO3 photocatalysts prepared with varying amounts of excess Ag and washed with different concentrations of HNO3 was examined. The water splitting activity of 5 mol% Ag-excess AgTaO3 improved significantly when treated with 13 M HNO3 for 1 h. While the AQE of overall water splitting was 20 % for the Rh0.5 CrO x /AgTaO3 prepared in a stoichiometric ratio, the Rh0.5 CrO x /AgTaO3 with excess Ag showed higher activity (AQE = 39 % at 254 nm) after washing with concentrated HNO3 . Graphical Abstract: ga1 Highlights: Valence-band-controlled AgTaO3 photocatalyst is active for water splitting reaction. AgTaO3 with excess Ag shows higher activity after HNO3 washing treatment. Excess Ag forms numerous metallic Ag particles on the AgTaO3 surface. Treatments using concentrated HNO3 remove the metallic Ag particles. Adding Ag in excess suppresses the formation of Ag + defects inside AgTaO3 .